2013
DOI: 10.1155/2013/547501
|View full text |Cite
|
Sign up to set email alerts
|

Are Mesenchymal Cells Indeed Pluripotent Stem Cells or Just Stromal Cells? OCT-4 and VSELs Biology Has Led to Better Understanding

Abstract: Stem cells have excited researchers because of their potential to regenerate. However, which stem cells will be the best candidate for regenerative medicine remains an enigma. Compared to pluripotent stem cells with associated risks of immune rejection and teratoma formation, adult stem cells especially the mesenchymal stem cells (MSCs) are hyped to be a suitable alternate since they also exhibit pluripotent properties. This review shows that there is a subpopulation of pluripotent very small embryonic-like st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 52 publications
0
43
1
Order By: Relevance
“…; Nam et al. ), due to its relatively limited potential, it is suggested that future studies would more likely involve the use of cells of higher potency such as pluripotent stem cells (Bhartiya ). Thus, the use of NT in MSCs provides opportunities to improve this and pave new possibilities for its applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Nam et al. ), due to its relatively limited potential, it is suggested that future studies would more likely involve the use of cells of higher potency such as pluripotent stem cells (Bhartiya ). Thus, the use of NT in MSCs provides opportunities to improve this and pave new possibilities for its applications.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and characterization of stem cells derived from various tissues and sources were carried out to demonstrate that MSCs are present and have specific characteristics. Although many studies have described the use of MSCs for various applications (Murphy et al 2003;Nam et al 2013), due to its relatively limited potential, it is suggested that future studies would more likely involve the use of cells of higher potency such as pluripotent stem cells (Bhartiya 2013). Thus, the use of NT in MSCs provides opportunities to improve this and pave new possibilities for its applications.…”
Section: Discussionmentioning
confidence: 99%
“…While application of embryonic stem cells (ESCs) is associated with immune rejection and teratoma formation, alternatively proposed mesenchymal stem cells (MSCs) have several advantages for the implementation in regenerative medicine (Ferro et al, 2012;Bhartiya, 2013). Ethical and easy isolation of MSCs from adult tissues, their involvement in tissue regeneration due to differentiation capacity and immunosupressive properties, are among the most important ones (da Silva Meirelles et al, 2006;Bhartiya, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ethical and easy isolation of MSCs from adult tissues, their involvement in tissue regeneration due to differentiation capacity and immunosupressive properties, are among the most important ones (da Silva Meirelles et al, 2006;Bhartiya, 2013). Bone marrow mesenchymal stem cells (BMMSCs) were first defined and considered for treatment of graft-versus-host-disease, hematological malignancies, neurologic and cardiovascular diseases, autoimmune diseases, both in autollogous and allogeneic settings (Ikebe and Suzuki, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These stem cells have been recently reviewed [22,23]. They also comprise a sub-population among mesenchymal stem cells [24]. Table 1 is a compilation of various properties of cancer stem cells and various reports showing that VSELs exhibit similar properties.…”
Section: Vsels Are Pluripotent Stem Cells In Adult Tissuesmentioning
confidence: 99%